Chemical Characterization, Analgesic, Antioxidant, and Anticholinesterase Potentials of Essential Oils From Isodon rugosus Wall. ex. Benth - Sadiq, Abdul; Zeb, Anwar; Ullah, Farhat; Ahmad, Sajjad; Ayaz, Muhammad; Rashid, Umer; Muhammad, Noor (Frontiers in Pharmacology, 2018)
Isodon rugosus Wall. ex. Benth is an important species and is used in folk medicine for different types of pains such as abdominal pain, earache, toothache, gastric and generalized body pain. Recently, we also have reported the antinociceptive potential of chloroform fraction of I. rugosus. In this research, we have investigated the antinociceptive, antioxidant and anti-cholinesterase potentials of essential oils from I. rugosus (Ir.EO), and have determined a possible mechanism of anti-nociception. The Ir.EO was subjected to gas chromatography-mass spectroscopy analysis to find out its chemical constituents. The Ir.EO was assayed for analgesic potential following acetic acid induced writhing, formalin test and hot plate method in animal models. The antioxidant activity was conducted against DPPH and ABTS free radicals following spectroscopic analysis. The cholinesterase inhibitory assays were performed using Ellman's assay. The GC-MS analysis of Ir.EO revealed the identification of 141 compounds. Ir.EO demonstrated strong antinociceptive potential in all three in-vivo models. With the use of nalaxone, it was confirmed that the essential oil was acting on the central pathway of nociception. The Ir.EO also exhibited strong free radicals scavenging potential, exhibiting IC50 values of 338 and 118 µg/ml for DPPH and ABTS free radicals respectively. In AChE and BChE inhibitory assays, the observed IC50 values were 93.56 and 284.19 µg/ml respectively. The encouraging antinociceptive, antioxidant and anticholinesterase results revealed that Ir.EO is a rich source of bioactive compounds as obvious from the GC-MS results.